2020
DOI: 10.1111/pim.12719
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic acid acts upon Leishmania donovani arresting cell cycle and modulating cytokines and nitric oxide in vitro

Abstract: Aims Visceral leishmaniasis (VL), caused by Leishmania donovani in India, is fatal if untreated, having serious concern of limited chemotherapeutic options. In this study, we evaluated antileishmanial efficacy of purified chlorogenic acid (CGA) against promastigotes and intracellular amastigotes infected into RAW264.7 macrophages. Methods and Results Chlorogenic acid was effective both on promastigotes (IC50 = 78.394 µmol/L, i.e. 27.75 µg/mL) and intracellular amastigotes (ED50 = 26.752 µmol/L, i.e. 9.47 µg/mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…It has been demonstrated that Leishmania clearance was enhanced by the Th1-type response, in which IL-12 expression played a crucial role [49]. Consistent with this, an increase in IL-12, TNF and NO production by macrophages was shown to be characteristic of an efficient anti-parasitic response [50]. In addition, immunotherapy with IL-12 was reported to mediate the control of L. major infection in BALB/c mice and was associated with wound healing promotion, parasite burden reduction and IL-4 downregulation [43].…”
Section: Discussionmentioning
confidence: 60%
“…It has been demonstrated that Leishmania clearance was enhanced by the Th1-type response, in which IL-12 expression played a crucial role [49]. Consistent with this, an increase in IL-12, TNF and NO production by macrophages was shown to be characteristic of an efficient anti-parasitic response [50]. In addition, immunotherapy with IL-12 was reported to mediate the control of L. major infection in BALB/c mice and was associated with wound healing promotion, parasite burden reduction and IL-4 downregulation [43].…”
Section: Discussionmentioning
confidence: 60%
“…After 48 h of CGA treatment, the protoflagella of Leishmania changed into a spherical shape, the flagella disappeared, the exercise capacity decreased, the metabolic activity decreased, and the growth reversed. In the logarithmic phase, the researchers discovered that the growth of flagella at the G1/S checkpoint was significantly blocked ( 87 ). Fusarium is one of the causes of rot and spoilage of fruits and vegetables.…”
Section: The Biological Activity and Mechanism Of Chlorogenic Acidmentioning
confidence: 99%
“…In addition, CGA could exert antifungal effects on Candida albicans by affecting fungal cell membranes (Sung & Lee, 2010). Additionally, it was reported that CGA could inhibit Leishmania , indicating that CGA may be a potential antiparasitic drug (Majumder et al, 2020). Wang et al (2017) reported that CGA could inhibit liver fibrosis induced by schistosomiasis and may serve as an antifibrotic drug for schistosomiasis liver fibrosis.…”
Section: Main Bioactive Functions Of Cgamentioning
confidence: 99%